PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA LEMBAGA PENJAMINAN MUTU PENDIDIKAN PROVINSI SULAWESI TENGGARA - Muhammad Basri (Universitas Halu Oleo, 2019)
ABSTRACTThe Problem that will be worked through deep observational is aff motivation effect and organization climate to employee performance at Educational Quality Guarantee Institute of Southeast Sulawesi Province. This research variables analyze motivation which covers identification dimension, employee placement appropriately, attention to employee self-respect, attention to work condition and give chance to go forward. Whereas, a variable of Organizational climate cover privacy aspect and acclimatization harmony, reward on employee work and their job clarity. While employee performance covers job sharpness. There is dimension even of clerk performance cover job quality, job quantity and also work time timing. Population in this research is overall of employee which amount 123 person, and this research design use data collection technic by use of questioner, interview and documents study. Whereas data analysis to hypothesis test by use of double linear regression analysis and partial analysis uses t-tests t and simultan analysis uses f-test The result of this research pointed out that 1) Motivation was positively influence to employee performance. 2) Organizational Climate was positively influencing to employee performance. 3) Motivation and organizational climate positive ly influence toward employee performance simultaneously on Educational Quality Guarantee Institute of Southeast Sulawesi Province as big as 27,30%. Meanwhile, 72,70% regarded by other factors. Keywords: Motivation, Organizational climate, and employee performance